A Generalized of Nörlund Ideal Convergent Double Sequence Spaces (2021)
In this paper, by using the Nörlund mean Nt and the notion of ideal double convergence, we introduce new sequence spaces c I2 0 (Nt ), cI2 (Nt ), and ℓ I2∞(Nt ). Besides, we study some topological and algebraic properties on these spaces. Furthermore, some inclusion concerning these spaces are proved.